Organic spectroscopic analysis - Anderson, Rosaleen J. (Tutorial chemistry texts, 2004)
This introduction to organic spectroscopic analysis aims to provide the reader with a basic understanding of how nuclear magnetic resonance (NMR), infrared (IR) and ultraviolet-visible (UV-Vis) spectroscopy, and mass spectrometry (MS) give rise to spectra, and how these spectra can be used to determine the structure of organic molecules. The text aims to lead the reader to an appreciation of the information available from each form of spectroscopy and an ability to use spectroscopic information in the identification of organic compounds. Aimed at undergraduate students, Organic Spectroscopic Analysis is a unique textbook containing large numbers of spectra, problems and marginal notes, specifically chosen to highlight the points being discussed. Ideal for the needs of undergraduate chemistry students, Tutorial Chemistry Texts is a major series consisting of short, single topic or modular texts concentrating on the fundamental areas of chemistry taught in undergraduate science courses. Each book provides a concise account of the basic principles underlying a given subject, embodying an independent-learning philosophy and including worked examples.